Two new species of Rhombognathus (Halacaridae, Trombidiformes) from a Mangrove in the northern littoral zone of São Paulo State (Brazil) - Pepato, Almir R.; Silveira, Paulo Sergio Amorim Da (Zootaxa, 2015)
Two species belonging to the algivorous genus Rhombognathus are described from algae associated to mangrove trees. Rhombognathus aribus sp. nov. is similar to R. major Bartsch, 2005, but may be set apart by the lacking of the third pair of dorsal setae on Ocular plates, adjunct setae on Posterior Epimeral plates, absence of ventral setae on basifemura III–IV and presence of ventromedial bipectinate setae on tibiae II of all individuals and on tibiae III of most of them. Rhombognathus picinguabensis sp. nov. shares the leg chaetotaxy and shape of the lateral claws with R. parvulus Viets, 1939. The latter species, however, can be easily separated from the former due the fusion of all dorsal plates in a single dorsal shield.